The Relationship Between Knowledge Levels and Attitudes Toward Reading Nutrition Facts Labels and the Prevalence of Prediabetes Among Adolescents - Adinda Eka Devita Sari; Nafilah Nafilah; Ardian Candra Mustikaningrum; Triya Ulva Kusuma (Poltekkes Kemenkes Semarang, 2026)
Background: Knowledge and attitudes toward reading nutrition facts labels are important factors in the prevention of metabolic diseases, particularly prediabetes. Adolescents, as a vulnerable age group, often pay limited attention to nutritional information on food packaging, thereby increasing the risk of unhealthy dietary behaviors. Objective: This study aimed to analyze the relationship between the level of knowledge and attitudes toward reading nutrition facts labels and the incidence of prediabetes among adolescents aged 16–18 years. Methods: A cross-sectional study was conducted among 62 adolescents aged 16–18 years in Weleri, selected using a simple random sampling technique. The research instruments included questionnaires assessing knowledge of nutrition facts labels and attitudes toward reading nutrition facts labels, as well as random blood glucose testing to determine prediabetes status. Data were analyzed using the Chi-square test with a significance level of 0.05. Results: The findings showed that most respondents had poor knowledge of nutrition facts labels (54.8%) and poor attitudes toward reading nutrition facts labels (56.5%). The prevalence of prediabetes among adolescents in this study was 53.2%. There was a significant association between knowledge level (OR = 0.047; 95% CI = 0.013–0.172; p = 0.000) and attitudes toward reading nutrition facts labels (OR = 0.021; 95% CI = 0.005–0.096; p = 0.000) and the incidence of prediabetes among adolescents. Conclusion: The Chi-square test results demonstrated a significant relationship between knowledge of nutrition facts labels and the incidence of prediabetes (p = 0.000), as well as between attitudes toward reading nutrition facts labels and the incidence of prediabetes (p = 0.000).